Problemtika Perbedaan Ukuran Luas Tanah Antara Sertipikat Tanah dengan Fakta di Lapangan (Deposisi: Jurnal Publikasi Ilmu Hukum, 2025)
This journal is entitled Problems of Differences in Land Area Size Between Land Certificates and Facts in the Field. Regulations regarding land ownership are regulated in such a way by the government, but the regulations issued at this time still cannot protect the rights of land owners because until now there are still many problems regarding differences in land area size between land certificates and facts in the field. The purpose of this study is to determine and analyze the causes of changes in land area size in land certificates and efforts to resolve if there is a difference in land area size between land certificates and facts in the field. The method used in this study is empirical legal research, which is a study that will later use empirical facts taken from human behavior through direct observation. The results of the study state that changes in land area size in land certificates are caused by two (2) factors, namely human factors and natural factors. Meanwhile, the resolution if there is a change in land area size in land certificates can be resolved through litigation and non-litigation.